2014
DOI: 10.1080/09602011.2014.964731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cognitive rehabilitation intervention on neuropsychiatric symptoms in mild to moderate Alzheimer's disease

Abstract: The main goal of this study was to evaluate the impact of a cognitive rehabilitation programme on 12 behavioural and psychological symptoms of dementia (BPSD) in patients with mild to moderate Alzheimer's disease (AD). This six-month single-blind block-randomised cross-over controlled study was conducted with 15 mild to moderate AD participants and their caregivers. All participants received a four-week home-based cognitive rehabilitation programme to learn/re-learn an instrumental activity of daily living. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
2
18
0
5
Order By: Relevance
“…The result showed that screening for hearing impairment and treatment of modifiable cause; for example, use of hearing aid, might enhance the effect of the intervention. Interestingly, previous work has shown that non‐pharmacological intervention can also worsen BPSD, especially behavior symptoms, which might be attributed to increasingly perceived environmental stress, and hearing impairment can be one of the possible explanations . In addition, communication impairment did not moderate the effect of intervention in the final analysis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The result showed that screening for hearing impairment and treatment of modifiable cause; for example, use of hearing aid, might enhance the effect of the intervention. Interestingly, previous work has shown that non‐pharmacological intervention can also worsen BPSD, especially behavior symptoms, which might be attributed to increasingly perceived environmental stress, and hearing impairment can be one of the possible explanations . In addition, communication impairment did not moderate the effect of intervention in the final analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, previous work has shown that non-pharmacological intervention can also worsen BPSD, especially behavior symptoms, which might be attributed to increasingly perceived environmental stress, and hearing impairment can be one of the possible explanations. 22,33 In addition, communication impairment did not moderate the effect of intervention in the final analysis. Though the result was possibly related to the type of intervention, it implied that participants with communication impairment should not be precluded from the intervention Despite all the efforts that went into the present study, there were several limitations.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, music therapy, physical activities, art-cognitive activities, and orientation training had favorable outcomes on delusions and hallucinations 39;40 . Home-based cognitive rehabilitation programs for patients with mild to moderate AD have also been shown to significantly reduce delusions 41 . Thus, non-pharmacologic approaches, while not established as preventative, could be considered to prevent or delay psychosis onset in AD 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive interventions may also contribute to improvements in the QoL of patients with DM1 because neuropsychological rehabilitation and cognitive remediation have been effective in decreasing impairments associated with other neurological conditions. [50][51][52] In addition, apathy may mediate the influence of cognitive function on QoL, which suggests that the reduction of apathy could lead to better cognitive performance or vice versa. 53 Depression and fatigue are the core predictors of psychological and physical QoL in patients with muscular diseases.…”
Section: Relationships Among Cognitive Function Psychologicalmentioning
confidence: 99%